Regulirovanie prav i obyazannostei ucheastnikov otnoshenii v sfere fizicheskoi kul'tury i sporta "O fizicheskoi kul'ture i sporte v Rossiiskoi federatsii" (Pravovye problemy) - Putalova, I. B. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The Federal Low "To physical culture and sport in Russian Federation", accepted by State Duma and subscribed by President at 04.29.1999, establishes legislative, organizational, economical and social bases of sport and leasure organizations, determines the principles of state politics in feild of physical culture, sport and the Olympic movement in Russia. The main purpose of this artical was to pay attantion at some points of the new Low, which are in contradictions with current norms of russian legislation. Author found ireous disadvantages in different parts of the Low, for instance, in points of legal status of the athlete, of judicial relationships regulation between athlete and sport organizations, of social prosecution of athlete and so on. However, as author noted, the problems analyzed by the article, do not decrease quality of the Low and its significance for physical culture and sport development in Russia.